The Buddhist philosophy as presented in Mīmāṁsā-śloka-vārttika - Vijaya Rani (Parimal Publications, 1982)
Study of the Buddhist philosophy as presented in Kumārila Bhaṭṭa's Ślokavārttika, 7th century exegesis of Śabarasvāmī's Mīmāṃsābhāṣya, commentary on Jaimini's Mīmāṃsāsūtra.